2013
DOI: 10.1111/weng.12032
|View full text |Cite
|
Sign up to set email alerts
|

More onKena‐passives in Singapore English

Abstract: In the so‐called kena‐passive construction in Singapore English (Bao and Wee ), the morphosyntactic realization of the passive feature of irregular verbs is optional (John kena caught/?catch) in contrast to the obligatory realization of the same feature within the English‐derived be‐passive (John was caught/*catch). We propose that this asymmetry follows from the hybrid syntactic structures of the kena‐passive construction. Specifically, we argue that the verb kena allows not only the standard passive structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Passive constructions have attracted the attention of linguists in world Englishes research for various reasons. On the one hand, there is evidence of structural borrowing, as is the case with the kena‐ passive in Singaporean English (see Fong, 2004: 97–98 or Kim & Sato, 2013). On the other hand, various studies have observed differences in the frequency of be ‐ and get ‐passives, not only across different varieties of English world‐wide but also across the written vs. spoken mode.…”
Section: Introductionmentioning
confidence: 99%
“…Passive constructions have attracted the attention of linguists in world Englishes research for various reasons. On the one hand, there is evidence of structural borrowing, as is the case with the kena‐ passive in Singaporean English (see Fong, 2004: 97–98 or Kim & Sato, 2013). On the other hand, various studies have observed differences in the frequency of be ‐ and get ‐passives, not only across different varieties of English world‐wide but also across the written vs. spoken mode.…”
Section: Introductionmentioning
confidence: 99%
“…Kachru, Y. Kachru, and Nelson 2008: xvii). In South East Asia where Vietnam is geographically located, there have been numerous studies regarding localised varieties of English, such as Thai English (Watkhaolarm 2005), Singapore English (Tan-Chia, Fang, and Ang 2013; Kim and Sato 2013;Smakman and Wagenaar 2013), and Malaysian English (Gut, Pillai, and Don 2013). In Vietnam, despite the significant status, features and functions of English used in written business communication, there is a dearth of empirical studies about these issues (Bautista and Gonzalez 2008).…”
Section: Introductionmentioning
confidence: 99%